Confirmation bias affects user perception of knee braces. (25th June 2018) - Balsamo, Brittany; Geil, Mark D.; Ellis, Rebecca; Wu, Jianhua
Abstract: Technological advances in orthopedic devices such as prostheses and orthoses are intended to improve function but may also result in increased complexity and expense. Consequently, accurate determination of effectiveness is important. When devices with advanced technology are used, it is possible that confirmation bias – the tendency for a user to actually experience what he or she expects to experience – will influence outcomes. This study assessed confirmation bias in 18 healthy young adults walking in knee braces. Participants wore two identical braces, but one was cosmetically modified and participants were told that it was a prototype computerized brace that could dynamically alter its stiffness. Before using the braces, the majority of users indicated a preference for the "computerized" brace. Actual walking showed no differences between the two braces. Following walking, users maintained preference for the "computerized" brace, indicating the presence of confirmation bias. These results underscore the importance of blinding when self-reported outcomes are used and the need to consider a placebo effect when comparing orthopedic devices.